Suppression of Heregulin-β1/HER2-Modulated Invasive and Aggressive Phenotype of Breast Carcinoma by Pterostilbene via Inhibition of Matrix Metalloproteinase-9, p38 Kinase Cascade and Akt Activation. (14th February 2011) - Pan, Min-Hsiung; Lin, Ying-Ting; Lin, Chih-Li; Wei, Chi-Shiang; Ho, Chi-Tang; Chen, Wei-Jen
Abstract : Invasive breast cancer is the major cause of death among females and its incidence is closely linked to HER2 (human epidermal growth factor receptor 2) overexpression. Pterostilbene, a natural analog of resveratrol, exerts its cancer chemopreventive activity similar to resveratrol by inhibiting cancer cell proliferation and inducing apoptosis. However, the anti-invasive effect of pterostilbene on HER2-bearing breast cancer has not been evaluated. Here, we used heregulin- β 1 (HRG- β 1), a ligand for HER3, to transactivate HER2 signaling. We found that pterostilbene was able to suppress HRG- β 1-mediated cell invasion, motility and cell transformation of MCF-7 human breast carcinoma through down-regulation of matrix metalloproteinase-9 (MMP-9) activity and growth inhibition. In parallel, pterostilbene also inhibited protein and mRNA expression of MMP-9 driven by HRG- β 1, suggesting that pterostilbene decreased HRG- β 1-mediated MMP-9 induction via transcriptional regulation. Examining the signaling pathways responsible for HRG- β 1-associated MMP-9 induction and growth inhibition, we observed that pterostilbene, as well as SB203580 (p38 kinase inhibitor), can abolish the phosphorylation of p38 mitogen-activated protein kinase (p38 kinase), a downstream HRG- β 1-responsive kinase responsible for MMP-9 induction. In addition, HRG- β 1-driven Akt phosphorylation required for cell proliferation was also suppressed by pterostilbene. Taken together, our present results suggest that pterostilbene may serve as a chemopreventive agent to inhibit HRG- β 1/HER2-mediated aggressive and invasive phenotype of breast carcinoma through down-regulation of MMP-9, p38 kinase and Akt activation.